MENGUJI PERUBAHAN KUALITAS AKRUAL DAN RELEVANSI NILAI LAPORAN KEUANGAN SEBELUM DAN SESUDAH FULL ADOPSI IFRS - KURNIA PUTRI, FIRSTY Kurnia (Jurnal Akuntansi AKUNESA, 2014)
This research to examine the accounting information that measured by the variableof accruals quality and value relevance.The test of Accrual quality and value relevance to prove there are any impact ofPSAK with full adoption IFRS standards, the expect is to improve the quality of accounting information and financial statements.The research, accrual quality useequations of Total Current Accrual and value relevance use the value of Earning Per Share (EPS) and Book Value (BV). The object of this research is manufacturing companies listed in Indonesia Stock Exchange in 2007-2013, and qualified by purposive sampling,so there are  71 vendors. This Research use Paired T-Test analysis. The results showed there are differences in the quality of accounting information on the variable quality and relevance value accrual period before (2007-2009) and after (2011-2013) the full adoption of IFRS.   Keywords: Accuals quality, relevance value, IFRS